2020
DOI: 10.26740/mathedunesa.v9n2.p392-401
|View full text |Cite
|
Sign up to set email alerts
|

Profil Kemampuan Pemecahan Masalah Matematika Siswa SMP Pada Materi Segiempat Ditinjau Dari Tipe Kepribadian Ekstrovert-Introvert

Abstract: Masalah merupakan pertanyaan yang dihadapi ketika tidak dapat diselesaikan dengan prosedur rutin. Untukmenyelesaikan masalah matematika membutuhkan analisis atau prosedur lain. Masalah matematika yangsering dijumpai dalam kehidupan salah satunya yaitu masalah segiempat. Menurut Polya, terdapat empatfase proses pemecahan masalah, yaitu memahami masalah, membuat perencanaan, melaksanakanperencanaan, dan memeriksa kembali. Terdapat salah satu faktor yang memengaruhi kemampuanpemecahan masalah, yaitu kepribadian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The data collected from the results of the analysis carried out by the author on several data sources found, then the overall data obtained to see the connection of mathematical abilities when viewed from the extrovert-introvert personality type through various models / strategies / learning approaches. Based on the results of a review of literature sources, the results of relevant research are (1) Research written by Putri & Masriyah (2020) Based on Table 3. above, it can be concluded that students with introverted personality types are able to carry out problem-solving steps correctly, so that they get results as expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data collected from the results of the analysis carried out by the author on several data sources found, then the overall data obtained to see the connection of mathematical abilities when viewed from the extrovert-introvert personality type through various models / strategies / learning approaches. Based on the results of a review of literature sources, the results of relevant research are (1) Research written by Putri & Masriyah (2020) Based on Table 3. above, it can be concluded that students with introverted personality types are able to carry out problem-solving steps correctly, so that they get results as expected.…”
Section: Resultsmentioning
confidence: 99%
“…2. Able to draw up a conclusion from the given problem.Based on the results of research conducted byPutri & Masriyah, (2020) obtained results and discussions regarding the profile of junior high school students' mathematical problem solving abilities on rectangular material in terms of extrovert and introvert personality types. The Mathematical Problem Solving Skills in Quadrilateral Material with Extovert Personality Type Table2above, it is concluded that extrovert students are not able to carry out problem solving steps properly and correctly.…”
mentioning
confidence: 99%
“…Peserta didik memiliki cara yang berbedabeda dalam memecahkan masalah, sehingga penting bagi pendidik untuk mengetahui kepribadian peserta didik (Isroil et al 2017;Ningsih & Awalludin, 2021). Putri & Masriyah (2020) Ha : rata-rata nilai matematika mahasiswa pendidikan fisika yang memiliki kepribadian guardian, idealis, rasional,dan artisan berbeda Jika diperoleh kesimpulan bahwa rata-rata nilai matematika sama, maka pengujian dilanjutkan ke analisa perbandingan ganda. Dimana perumusan hipotesa pada uji perbandingan ganda adalah sebagai berikut.…”
Section: Mandalika Mathematics and Education Journal Volume 4 Nomor 2...unclassified
“…Adapun penelitian yang dilakukan oleh Arini (2016) menyatakan bahwa siswa extrovert maupun introvert mampu mengolah informasi, namun siswa extrovert belum mampu mengketerkaitkan informasi yang ada. Subjek introvert lebih berhati-hati dan teliti di bandingkan siswa extrovert karena siswa extrovert memiliki hasil perhitungan dan hasil yang salah.…”
Section: Pendahuluanunclassified